Measurement of signal-to-noise ratio (SNR) in off-axis particle holography using paraxial approximation - Tamrin K. F., Rahmatullah Bahbibi, Samuri S. M. (N/A, 2014)
Measurement of signal-to-noise ratio (SNR) in off-axis particle holography using paraxial approximation by Tamrin K. F., Rahmatullah Bahbibi, Samuri S. M.,